1991
DOI: 10.1159/000261359
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Xylitol Consumption and Mutans Streptococci in Plaque and Saliva

Abstract: The effect of 4 to 6 years of habitual use of xylitol gum (≥ 2 times per day) on the viable counts of mutans streptococci in both plaque and saliva was evaluated in a cross-sectional study of participants of the Ylivieska xylitol study (Finland, 1982–1984). Paraffin-stimulated saliva was collected first, whereafter the remaining plaque was collected from all available tooth surfaces and pooled. The habitual xylitol consumers (n = 15) had less plaque than the controls (n = 21). The total viable counts of mutans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 10 publications
3
34
0
1
Order By: Relevance
“…Loesche et al (1984) previously found that children given 5 g xylitol/day for 4 wks had reduced saliva and plaque S. mutans levels compared with baseline. Other longterm clinical studies did not find reductions in plaque S. mutans (Makinen et al, , 1996Söderling et al, 1991).…”
Section: Introductionmentioning
confidence: 79%
“…Loesche et al (1984) previously found that children given 5 g xylitol/day for 4 wks had reduced saliva and plaque S. mutans levels compared with baseline. Other longterm clinical studies did not find reductions in plaque S. mutans (Makinen et al, , 1996Söderling et al, 1991).…”
Section: Introductionmentioning
confidence: 79%
“…2,4 Other evidence has shown that xylitol leads to a reduction in the quantity of plaque, possibly by interfering with mechanisms of adhesion between plaque organisms and the tooth's surface. [65][66][67][68] This is the most likely explanation for the reduced colonisation of mutans streptococci in the mouths of these children.…”
Section: Specific Caries-preventive Actions Of Xylitolmentioning
confidence: 95%
“…Habitual long-term xylitol consumption appears to select for natural mutant cells of MS which are 'xylitol-resistant' [Trahan and Mouton, 1987]. Xylitol-resistant mutants appear to shed more easily into saliva from plaque than do xylitol-sensitive parental strains [Söderling et al, 1991;Trahan et al, 1992]. We have reported earlier that habitual xylitol consumption by mothers was associated with a statistically significant reduction in the probability of mother-child transmission of MS assessed at 2 years of age.…”
mentioning
confidence: 90%